A Survey of Resources for Vision Rehabilitation in Schools for the Blind in Rural South-Eastern Nigeria: Any Implications for Eye Care Policy? - Charles O. Anyalebechi; Stella N. Onwubiko; Nkiru Z. Nwachukwu; Cyril C. Mamah; Ferdinand C. Maduka-Okafor; Ernest N. Onwasigwe; Rich E. Umeh (International Journal of Medicine and Health Development, 2025)
Background: Blindness has profound consequences on the individual, family and society. Rehabilitation improves the quality of life in persons living with disability. Objectives: To assess the resources available for vision rehabilitation in schools for the blind, their impact on the students, and factors influencing their availability in rural South-East Nigeria. Materials and Methods: A descriptive, cross-sectional study design using both quantitative and qualitative approaches was adopted for this survey. A checklist was used to assess the resources in the three schools for the blind located in Enugu, Anambra, and Abia States, all in South-East Nigeria. An in-depth interview was held with the head teachers to investigate the factors influencing their availability. Focus group discussions with a convenient sample of students from each school were conducted to ascertain the accessibility of resources and their impact. Descriptive statistics was used to summarize data. Discussions and interviews were recorded, transcribed, and analyzed using the Braun and Clarke guide to thematic content analysis. Results: There was a total of 215 students in the three schools of the blind. The resources for rehabilitation in these schools were inadequate. Braille was the predominant material resource. Computerized assistive devices were non-existent. The number of teachers was insufficient, with limited offers in Nigerian Universities on special education. However, available educational devices, daily living devices, and personnel were accessible to the students and impacted positively on them. Funding was the main factor affecting availability of the resources. Conclusion: There was a lack of resources for rehabilitation. The reported deterrent is amenable to even resource allocation by governmental and donor agencies. These data serve to guide policymakers on measures to improve the blind students’ quality of life.